2017
DOI: 10.1161/circep.116.004419
|View full text |Cite
|
Sign up to set email alerts
|

First-in-Man Analysis of the Relationship Between Electrical Rotors From Noninvasive Panoramic Mapping and Atrial Fibrosis From Magnetic Resonance Imaging in Patients With Persistent Atrial Fibrillation

Abstract: Background-Late gadolinium enhancement (LGE) cardiovascular magnetic resonance (CMR) imaging can be used to evaluate characteristics of atrial fibrosis. The novel noninvasive epicardial and endocardial electrophysiology system (NEEES) allows for the identification of sources with rotor activity. This study describes a new technique to examine the relationship between rotors and LGE signal intensity in patients with persistent atrial fibrillation (PERS) scheduled for ablation. Methods and Results-Ten consecutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 32 publications
(49 reference statements)
4
27
0
Order By: Relevance
“…Atrial fibrosis has been proposed as one mechanism for rotor clustering, and whereas a correlation between the amount of late gadolinium enhancement detected by MRI and the number of regions exhibiting reentry has been shown (8), other studies have found no such correlation (9,10). A role for APD heterogeneity in the genesis of rotors has been shown in in vitro cell culture studies of virally transduced ventricular myocyte monolayers variably expressing the hERG (human ether-a-gogo-related gene) protein in neonatal rats.…”
Section: Introductionmentioning
confidence: 99%
“…Atrial fibrosis has been proposed as one mechanism for rotor clustering, and whereas a correlation between the amount of late gadolinium enhancement detected by MRI and the number of regions exhibiting reentry has been shown (8), other studies have found no such correlation (9,10). A role for APD heterogeneity in the genesis of rotors has been shown in in vitro cell culture studies of virally transduced ventricular myocyte monolayers variably expressing the hERG (human ether-a-gogo-related gene) protein in neonatal rats.…”
Section: Introductionmentioning
confidence: 99%
“…Catheters with close inter-electrode Two hundred twenty-four unipolar surface electrodes are used to acquire electrograms that are projected on magnetic resonance imaging atrial shells to detect rotors. 132,133 FIRM: focal impulse and rotor mapping; 3D: three-dimensional. spacing resulting in improved spatial resolution may enhance our ability to detect rotors with confidence.…”
Section: Improvements In Mapping-seeing Is Believingmentioning
confidence: 99%
“…Late gadolinium enhancement is today a well-established method for detecting fibrosis in the ventricular myocardium [2]. Since its introduction in 2007 [3], CMR imaging of left atrial fibrosis with late gadolinium enhancement (LA LGE) has received increasing interest [4][5][6][7][8][9]. The method has proven valuable in detection of pre-ablation atrial fibrosis [4,8,[10][11][12][13] but also in evaluation of ablation procedures and detection of possible gaps in ablation lines after pulmonary vein isolation [10,12,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Despite its many promising possibilities, LA LGE has remained a method reserved for highly specialized centres and previous studies have reported both positive [4,8,14,15] as well as disappointing results [5,7,[16][17][18][19]. The clinical adoption of LA LGE has been slowed by complex image acquisition protocols reflected in high exclusion rates of scans in clinical studies (9-32%) [4,5,8,9,13,20] and furthermore of a lack of consensus on an objective image analysis method [21].…”
Section: Introductionmentioning
confidence: 99%